The Development of Problems Solving Skills of Grade 6 Students by Learning Management With K-W-D-L Techniques - Somwong, Thanida; Prasertsang, Parichart (Journal of Roi Et Rajabhat University, 2021)
The objectives of this research were : 1) to develop problem solving skills on the problem of fractions topic of grade 6 students who are learning based on the K-W-D-L techniques at least 70 percent of total students with the average scores of 70 percent up and 2) to study the satisfaction of grade 6 students towards learning management based on the K-W-D-L techniques in order to develop problem solving skills. The target group was grade 6 students in the second semester of the academic year 2019 at Ban Khok Klang (Woranat Prachasan) School. The instruments used in this research were 10 learning management plans based on K-W-D-L technique of grade 6 students, the ended-loop test of the problem solving skill, and form of recording the result of using plans and interview from. The data analysis used percentage, mean and standard deviation. The research findings were: 1) After developing the problem solving skills based on based on the K-W-D-L techniques, 100 percent of target students passed the criteria scores and had the skills of solving mathematic problem with the average scores at 70 percent up. 2) The average of grade 6 students’ satisfaction towards learning management based on the K-W-D-L techniques was at 4.79 and the overall satisfaction was at highest level.